"But not laughing": horsemanship and the idea of the cavalier in the writings of William Cavendish, first Duke of Newcastle. Issue 4 (2nd October 2017) - Chalmers, Hero
ABSTRACT: This article examines William Cavendish's two treatises on horsemanship printed in 1658 and 1667, respectively. It argues that a close reading of these works in their discursive and iconographic contexts reveals their engagement with a markedly unstable idea of the cavalier as horseman during this period and evinces a far greater degree of self-conscious anxiety concerning questions of governance than previous critics have acknowledged. In particular, it explores Newcastle's grappling with notions of the cavalier as frivolous man of pleasure and as a figure of monstrosity, conceived of in terms of a troubling hybridity with his horse. This leads to a specific consideration of the ambivalent role played by the figure of the centaur in Newcastle's equestrian writings, a figure whose contradictory antecedents are played out in its recurrence in the contemporary literature of political controversy.